If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5c + 3 = 29 Reorder the terms: 3 + 5c = 29 Solving 3 + 5c = 29 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5c = 29 + -3 Combine like terms: 3 + -3 = 0 0 + 5c = 29 + -3 5c = 29 + -3 Combine like terms: 29 + -3 = 26 5c = 26 Divide each side by '5'. c = 5.2 Simplifying c = 5.2
| 2x+2(x+6)=12 | | 3x^2-12x^2+36x=0 | | 4s-8=15 | | 2x^2-36x=720 | | 18+8x=88 | | (25x^2-100x+50)(50x-50)(2x)-(-100x)(5-5x)(10x^2)=0 | | 5/7x3/5 | | 5y-20+110+y=180 | | W-4.40=9.60 | | x=30+-1y | | (9y+3)(3x+10)= | | -6y+10x=134 | | 3(4+1)=8(-2x+3) | | 10sin(c)-cos(c)=8 | | 0=16z^3-z | | 1+3(9-6)-4= | | 2=-1.5(4)+b | | x-5-1=x-11/4 | | 6r=87 | | 2h^3+2h^2t-4ht^2= | | 20-4x+2x= | | 3x+14=260 | | 48=.7X | | 6x+8=31 | | 8+3d=10+5d | | 12n^2=15+12n | | (-4*2)+(-4*3b)+5b=13 | | x=1/2(3x-11) | | C+7+3c=5c+11 | | 0.3(x)=294 | | 9x+4x=22-6 | | 9m+63=27 |